(untitled) (GYMNASIUM, 2009)
The study undertaken aimed to highlight the link between the golden proportion and alignment of the lower limb, especially the foot, also finding a means for rapid assessment of foot position by using a tool that allows a rapid diagnosis of deviations, useful in practice, in the work of a physical therapist. The golden proportion, the result of golden section, in which the whole is divided into two unequal parts, so that the large part is mean proportional between the small part and whole, is found in the structure of the human body or in the structure of various parts of human body.